Presentation of Tools Helping to Set a Preservation Target for Displaying Light Sensitive Collection items - Christel Pesme (Nuevo mundo - Mundos Nuevos, 2016)
Relationships between color production, color rendering of indigenous American textiles and their historical, ethnological, social, symbolic, aesthetic meanings, were presented during the conference. This paper explores the subject of color stability in relation to preservation issues that become critical through display under museum or gallery conditions. The paper reviews the definitions and relationships between important concepts pertaining to lighting decisions for sensitive artifacts, such as damage function, “Preservation Target”, value function, color rendering and light-induced color change (terms to be explained, below). Recently developed tools in the conservation field and explorative approaches that can help in the design of an appropriate lighting policy for sensitive collection items are presented. Use of the microfade tester to assess the light sensitivity of collection items is described. The paper also describes how microfadotesting results can be used in combination with innovative visual tools based on model rendering of color in order to facilitate a decision on the establishment of the “Preservation Target” for a given collection item. Setting a Preservation Target is key to designing the appropriate lighting policy for sensitive collection items. In parallel, appropriate lighting policies strive to optimize the collection items perceived value by allowing viewers to experience it in the museum context, while minimizing risk of light induced degradation.